Bi-Gaussian Stratified Wetting Model on Rough Surfaces - Hu, Songtao (Langmuir : the ACS journal of surfaces and colloids, 2019)
Wetting mechanisms on rough surfaces were understood from either a monolayer or a multiscale perspective. However, it has recently been shown that the bi-Gaussian stratified nature of real surfaces should be accounted for when modeling mechanisms of lubrication, sealing, contact, friction, acoustic emission, and manufacture. In this work, a model combining Wenzel and Cassie theories was put forward to predict the static contact angle of a droplet on a bi-Gaussian stratified surface. The model was initially applied to numerically simulated surfaces and subsequently demonstrated on hydrophilic steel and hydrophobic self-assembled monolayer specimens with preset bi-Gaussian stratified topographies. In the Wenzel state, both the upper and the lower surface components are fully wetted. In the Cassie state, the upper component is still completely wetted, while the lower component serves as gas traps and reservoirs. By this model, wetting evolution was assessed, and the existence of different wetting states and potential state transitions was predicted